2004
DOI: 10.1037/0012-1649.40.4.572
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Identity Influence Children's Psychological Well-Being?

Abstract: This study examined influences of gender identity on change in preadolescents' adjustment over time. In each of two successive years, three measures of gender identity (felt gender typicality, contentment with gender assignment, and felt pressure for gender conformity) and four measures of adjustment (self-esteem, internalizing symptoms, externalizing symptoms, and acceptance by peers) were collected. Low gender typicality, low gender contentedness, and high felt pressure all foreshadowed deterioration on one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
183
3
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(201 citation statements)
references
References 29 publications
11
183
3
4
Order By: Relevance
“…In the twin study of Coolidge et al (2002), a significant correlation was found between GID and depression for non-referred children (r = .20), but the correlation between GID and separation anxiety was non-significant (r = .11). Yunger, Carver, and Perry (2004) also reported a negative association between gender typicality and Internalizing problems. These results suggest that gender atypical behavior is associated with increased levels of problem behaviors.…”
Section: Introductionmentioning
confidence: 98%
“…In the twin study of Coolidge et al (2002), a significant correlation was found between GID and depression for non-referred children (r = .20), but the correlation between GID and separation anxiety was non-significant (r = .11). Yunger, Carver, and Perry (2004) also reported a negative association between gender typicality and Internalizing problems. These results suggest that gender atypical behavior is associated with increased levels of problem behaviors.…”
Section: Introductionmentioning
confidence: 98%
“…Findings on gender differences in selfperceived gender typicality have been somewhat mixed. Some studies have found higher levels of selfperceived gender typicality among boys than girls (Bos & Sandfort, 2010;Carver et al, 2003;Egan & Perry, 2001;Yunger et al, 2004), whereas other studies have not found significant gender differences (Lamb et al, 2009;Smith & Leaper, 2006;Yu & Xie, 2010). Researchers have posited that the observed higher levels of gender typicality among boys may be due to greater pressure for gender conformity among boys (Egan & Perry, 2001) or the higher status of men and boys relative to women and girls (and of masculine to feminine activities and characteristics) in most cultures (Lurye, Zosuls, & Ruble, 2008).…”
mentioning
confidence: 94%
“…Second, the impact of gender typicality on adjustment may differ based on cultural factors. For example, cultural differences have been observed in children's judgments of the acceptability of cross-gender-typed behavior (Lobel, Gruber, Govrin, & Mashraki-Pedhatzur, 2001), and gender typicality may be more influential when pressure to conform to gender norms is high (Carver et al, 2003;Egan & Perry, 2001;Yunger et al, 2004). In addition, research on students from different ethnic groups within the United States suggests that the impact of gender typicality on adjustment may differ based on race and ethnicity (Corby et al, 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations